2020
DOI: 10.1186/s12885-020-07295-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-intensity interval training exercise on breast cancer survivors: a pilot study to explore fitness, cardiac regulation and biomarkers of the stress systems

Abstract: Background Cardiovascular disease (CVD) remains the largest cause of death in breast cancer survivors. The aim of this study was to explore the impact of exercise intensity on aerobic fitness and autonomic cardiac regulation (heart rate variability (HRV)) and salivary biomarkers of the stress systems (HPA-axis, cortisol; sympathetic nervous system, α-amylase) and mucosal immunity (secretory(s)-IgA), markers of increased risk of CVD in breast cancer survivors. Methods Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 69 publications
3
47
0
10
Order By: Relevance
“…In addition, cholinergic mechanisms within the inflammatory reflex have, in recent years, been implicated in attenuating obesity-related inflammation and metabolic complications. Recent evidence highlights the relationship among fitness, the autonomic nervous system and metabolic dysfunctions in BC, and their impact on the patient’s prognosis [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, cholinergic mechanisms within the inflammatory reflex have, in recent years, been implicated in attenuating obesity-related inflammation and metabolic complications. Recent evidence highlights the relationship among fitness, the autonomic nervous system and metabolic dysfunctions in BC, and their impact on the patient’s prognosis [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overweight and inactivity are also associated with chronic low-grade inflammation and metabolic dysfunction characterized by elevated levels of circulating proinflammatory mediators known to promote tumorigenesis and recurrences [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Indeed, metabolic syndrome accompanied by sedentary behaviors associated with being overweight have been established as notable risk factors for BCSs [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…The participants' peak power was determined using the maximal incremental cycle test prior to the 12-week intervention. Exercise intensity over the duration of the study was adjusted to ensure participants in the MICT group exercised within the prescribed range of 55-65% of peak power or the equivalent of between 9 and 13 on the modified Borg scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) as determined by the study investigators. The HIIT group similarly completed 5 min warm-up and cool-down periods at 50% peak power as determined by the pre-intervention maximal incremental cycle exercise test.…”
Section: Exercise Interventionmentioning
confidence: 99%
“…Prior research has demonstrated a strong correlation between increased cardiorespiratory fitness (VO2 peak ) and reduced cancer-related mortality [8]. Although current guidelines for cancer survivors recommend the performance of moderate-intensity aerobic exercise [9,10], recent evidence indicates that high-intensity interval training (HIIT) more effectively improves VO 2peak compared to moderate-intensity continuous training (MICT) in BC survivors (BCS) [11]. This dose-response relationship was illustrated well through the work of Jones et al [12], where MICT was unable to elicit significant alterations in plasma concentrations of IL-6, CRP, or TNF-α in BCS.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of HIIT protocols was prescribed and controlled based on percentage of maximal velocity achieved during incremental test (Vmax) [ [41,66] or reserve heart rate HR reserve [42], and percentage of peak power [25,26,44,51,58] or maximum anaerobic power [27]. Eleven studies prescribed SIT protocol using "all out" efforts [22][23][24]44,45,47,48,[52][53][54]63]. Characteristics of IT protocols are detailed in Tables 1 and 2.…”
Section: Intervention Characteristicsmentioning
confidence: 99%